소아에서 복강경하 요막관 낭종 절제술의 마취 관리 - 유장희; Jang Hee Lyu; 이경민; Kyoung Min Lee; 이승윤; Seung Yun Lee; 이준걸; Jun Geol Lee (Korean journal of anesthesiology, 2005)
A 14-month-old female patient was admitted for the laparoscopic excision of a complicated urachal cyst. General anesthesia was induced with thiopental and rocuronium and maintained with sevoflurane and the intermittent administration of vecuronium. During the insufflation of CO2 her intra-abdominal pressure was maintained below 12 cmH2O to avoid excessive hypercarbia. Thirty minutes after CO2 insufflation initiation, end tidal CO2 increased to 74 mmHg at a peak inspiratory airway pressure of 24 cmH2O. Laparoscopic excision of the urachal cyst was performed within 2 hours without a further change in end tidal CO2, blood pressure, heart rate, or O2 saturation. Before extubation, O2 saturation by pulse oxymetry was 99% and end tidal CO2 was 45-50 mmHg. The patient was discharged without any problem 5 days after the operation. We report on this clinical experience and include a brief review of the literature. KCI Citation Count: 1